Coordenação intermembros no alcance de objetos de lactentes típicos e com síndrome de Down - Cerra, Larissa Carvalho Vanzo (2012)
Research has shown that bimanual actions are demonstrative of the functional brain development; thus it is relevant to investigate how interlimb coordination develops in typically-developing infants, as well as in infants with impaired brain organization, such as in the presence of Down syndrome (DS). Objectives: The aims of this study were as follows: 1) to study the development of interlimb coordination in typically-developing infants (TD) and in infants with DS while reaching and grasping objects with different sizes; and 2) to investigate changes in the interlimb relations during the stages after reaching emergence. Methods: Reaching movements performed by 8 TD infants and 7 infants with DS were monthly recorded between the ages of 4 and 8 months. The frequency of categories used during movement initiation, object touching and grasping; the frequency of reaching and the contribution of each arm were calculated. The effects of object size and of the time after reaching onset were analyzed in intra- and inter-group comparisons. Results: TD infants were able to change the configurations used in the movement initiation, object touching and grasping; their interlimb coordination changed from synchronic reaches to asynchrony or unimanual trajectories, based on object properties. Infants with DS only changed their grasping configurations; the strategies they used were not optimally adjusted to object properties; difficulties to grasp the objects were also evident. Conclusions: With the experience in reaching, interlimb coordination in TD infants is increasingly modulated by object properties in an anticipatory way. Infants with DS seem to need a longer time to use sensory information and to modulate reaching and grasping configurations.